Studi Literatur: Predisposing, Enabling, dan Reinforcing Factors Terjadinya Perilaku Seksual Pranikah pada Remaja: PREDISPOSING FACTORS, ENABLING FACTORS, DAN REINFORCING FACTOR TERJADINYA PERILAKU SEKSUAL PRANIKAH PADA REMAJA : LITERATUR REVIEW - Hardiyati Hardiyati; Shelly Iskandar; Taty Hernawaty (Politeknik Kesehatan Kemenkes Mamuju, 2019)
Adolescent behaviors that have the potential to cause problems that often occur and are most prominent among adolescents are some high-risk behaviors including experiences of sexual violence and premarital sexual behavior. Changes that occur in adolescents ranging from physical, psychological, and social changes that risk causing problems because they are hanging out with peers and feel attracted to the opposite sex. The impact of sexual behavior on adolescents results in abortion, unwanted pregnancy, death, increased incidence of HIV/AIDS as well as an increase in juvenile crime in adolescents. The purpose of this literature study is to identify early predisposing factors, enabling factors, and reinforcing factors that influence premarital sexual behavior. The method used in writing this literature study with internet searches from Proquest, CINAHL, EBSCOHost, Pubmed, Google Scholar and nursing books from 2000 – 2014 with the keywords Premarital sexual behavior. Predisposing factors include dating status, dating frequency, and knowledge. Enabling factors include the use of smartphones and reinforcing factors are religious norms and family norms. It can be concluded that several factors that influence the occurrence of premarital sexual behavior include dating status, frequency of dating, knowledge, smartphone usage, religious norms and family norms. The high influence of premarital sexual behavior shows that health promotion programs must be focused on increasing positive and supportive values, as well as the need for skills training so that adolescents can avoid premarital sexual behavior.